Vibration analysis of 28 kHz horn transducer for ultrasonic cleaning based on harmonic response analysis - Suchada Phophayu; Jatuporn Thongsri (My University, 2022)
Abstract The Horn Transducer (HT) is one of the key components in ultrasonic applications, consisting of a front mass, piezoelectric, and back mass parts. Previously, most of the research focused on vibration study of the front mass part based on modal analysis, but the other parts were ignored; therefore, the research results have limitations to actual usage. This research presents the vibration analysis of HT included all parts, based on harmonic response analysis (HRA). First, a conventional HT of 28 kHz, 50 W, 220 V, front mass-radius ( R ) of 29 mm, and height ( H ) of 5 mm was investigated for the vibration analysis. Next, proposed designs were also investigated by varying the R as 27 mm - 32 mm, and H as 4 mm - 8 mm. All results were analyzed to find a suitable shape and investigated the designs that affected the vibration. The simulation results revealed that the longitudinal amplitude depends on R and H . In addition, the simulation results were consistent with an experiment and previous work. Finally, the suitable design with R of 29 mm and H of 7 mm provided the optimum vibration at 27,250 Hz. The outcomes of this research were applied to develop a high-performance ultrasonic cleaner.
Keywords: Harmonic; Ultrasound and Cavitation Phenomena